Constitutionality of the Use of Artificial Intelligence in Government Administrative Decision-Making: An Analysis of the Principle of Due Process of Law in Indonesia - Luh Putu Vera Astri Pujayanti (Yayasan Hisnul Muslim Lombok, 2025)
The rapid integration of Artificial Intelligence (AI) into public administration has fundamentally transformed governmental decision-making processes by enhancing efficiency, consistency, and the speed of public service delivery. However, the increasing reliance on algorithmic systems in administrative governance raises significant constitutional concerns, particularly in relation to transparency, accountability, procedural fairness, and the protection of citizens’ fundamental rights. This study aims to examine the constitutionality of AI-assisted administrative decision-making in Indonesia through the lens of the principle of due process of law. The research employs a qualitative legal research method with a normative-juridical approach. It focuses on constitutional principles, administrative law doctrines, statutory frameworks, and comparative legal developments concerning automated decision-making in the public sector. Data are collected through an extensive doctrinal analysis of constitutional provisions, legislation, judicial decisions, scholarly literature, and relevant policy documents addressing artificial intelligence and digital governance. The findings indicate that while AI-based systems provide substantial administrative benefits, their implementation introduces constitutional risks such as algorithmic opacity, limited explainability, potential discriminatory outputs, and weakened accountability mechanisms. These issues directly affect the realization of procedural justice, legal certainty, equality before the law, and access to effective legal remedies. The study further identifies that Indonesia’s current legal framework has not yet developed comprehensive constitutional safeguards specifically regulating the use of AI in administrative decision-making. As a key contribution, this study proposes a constitutional compliance framework consisting of six interrelated principles: legality, transparency, explainability, human oversight, accountability, and effective remedy. This framework is intended to serve as a normative benchmark for evaluating the constitutional legitimacy of AI deployment in public administration and to ensure that technological advancement remains aligned with the rule of law, democratic governance, and the protection of fundamental rights.